2019
DOI: 10.15244/pjoes/96262
|View full text |Cite
|
Sign up to set email alerts
|

Existence and Removal of Rotaviruses Group A and Cryptosporidium Species in a Wastewater Treatment Plant

Abstract: Rotavirus group A (RV-A) and Cryptosporidium spp. are recognized as important pathogens causing gastroenteritis, even with very low doses in all age groups and representing a public health risk. Seventy-two wastewater samples were collected and concentrated for detecting Cryptosporidium spp. and RV-A. PCR was performed for identification of genus Cryptosporidium using generic primers and species specific primers for Cryptosporidium parvum / Cryptosporidium hominis. Multiplex seminested RT-PCR was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Although person-to-person transmission is an important route, the main RoV transmission route is the faecal-oral route. More than 1000 RoV particles can be present in one gram of faeces, and these viruses have been detected at significant levels in wastewater in many countries, such as South Africa ( Adefisoye et al, 2016 , Osuolale and Okoh, 2017 ), Japan ( Yasui et al, 2016 ), Canada ( Qiu et al, 2016 ), the USA ( Schmitz et al, 2016 , Gerba et al, 2018 ), Tunisia ( Ibrahim et al, 2016 ), Italy ( Mezzanotte et al, 2016 ), France ( Kaas et al, 2019 ), Japan ( Kobayashi et al, 2017 ), Uruguay ( Lizasoain et al, 2018 ), Egypt ( Rizk et al, 2019 ), the UK ( Adriaenssens et al, 2018 ), Brazil ( Assis et al, 2018 ), New Zealand ( Gyawali et al, 2018 ), Canada ( Qiu et al, 2018 ), New Zealand ( Clemens et al, 2020 ), and Tunisia ( Ibrahim et al, 2020 ).…”
Section: Viruses: Genomes Classification and Infection Symptomsmentioning
confidence: 99%
“…Although person-to-person transmission is an important route, the main RoV transmission route is the faecal-oral route. More than 1000 RoV particles can be present in one gram of faeces, and these viruses have been detected at significant levels in wastewater in many countries, such as South Africa ( Adefisoye et al, 2016 , Osuolale and Okoh, 2017 ), Japan ( Yasui et al, 2016 ), Canada ( Qiu et al, 2016 ), the USA ( Schmitz et al, 2016 , Gerba et al, 2018 ), Tunisia ( Ibrahim et al, 2016 ), Italy ( Mezzanotte et al, 2016 ), France ( Kaas et al, 2019 ), Japan ( Kobayashi et al, 2017 ), Uruguay ( Lizasoain et al, 2018 ), Egypt ( Rizk et al, 2019 ), the UK ( Adriaenssens et al, 2018 ), Brazil ( Assis et al, 2018 ), New Zealand ( Gyawali et al, 2018 ), Canada ( Qiu et al, 2018 ), New Zealand ( Clemens et al, 2020 ), and Tunisia ( Ibrahim et al, 2020 ).…”
Section: Viruses: Genomes Classification and Infection Symptomsmentioning
confidence: 99%
“…The release of such poorly treated wastewater (i.e., not compliant with the Egyptian decree) into water bodies has negative impacts on humans and the environment in the short and long term. Several studies have reported a high level of human enteric parasites, bacteria, protozoa, and viruses in treated wastewater [14,17,41,[57][58][59]. There have been reports of cholera and diarrhea outbreaks in developing countries due to the drinking of wastewater-contaminated water [7,14,60].…”
Section: Discussionmentioning
confidence: 99%
“…The activated sludge treatment produced a mean log10 removal range of 2–2.83 while that of the coagulative precipitation method was 0.72 ± 0.08. Rizk et al 137 determined a total RV removal rate of 29.4% for a WWTP that uses chlorine for disinfection and operates with a trickling filter technology. A Canadian study by Qiu et al 67 revealed high concentrations of RVs by qPCR in both pre-UV and post-UV samples and the infectious form was also confirmed in 5.9% (3/51) of pre-UV samples and 8% (4/50) of post-UV samples by integrated cell culture with qPCR (ICC-qPCR).…”
Section: Survival and Factors Influencing Viral Persistence In The Aq...mentioning
confidence: 99%
“…101,120 In genotyping of RV-A in water samples, the multiplex RT-PCR is semi-nested. 137 The rst round of PCR usually involves amplication of the VP7 or VP4 gene sequences with the consensus oligonucleotide primers. The VP4 or VP7 amplicons are then used as a template in the second round of PCR with P-and G-type specic oligonucleotide primers targeting P [4], P [6], P [8], P [9], P [10] and P [11] or G1, G2, G3, G4, G8, G9, G10 and G11, respectively.…”
Section: Real-time Reverse Transcription Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
See 1 more Smart Citation